Dental management and consideration of patients with severe deforming, type III osteogenesis imperfecta in clinic: A case report. Issue 3 (December 2020) - Lai, Chun-Cheng; Chang, Hsiao-Hua; Wang, Yin-Lin; Huang, Guay-Fen
Abstract: Osteogenesis imperfecta (OI) is an autosomal dominant disorder not only influencing the musculoskeletal system but also dentition. This case is a 6 year 2 month old female suffering from severe deforming, type III OI, which is deathful due to frequent bone fractures and hyperthermia. We could observe very short stature, severe scoliosis, hunchback, and bowing of legs from appearance. She visited our clinic due to pain from multiple dental caries and complicated medical status. In the oral cavity, dentinogenesis imperfecta and constriction of maxilla were also presented. With multiple visits, pain was relieved and occlusion was re-established successfully.